2018
DOI: 10.1038/s41591-018-0254-9
|View full text |Cite
|
Sign up to set email alerts
|

A CD4+ T cell population expanded in lupus blood provides B cell help through interleukin-10 and succinate

Abstract: Understanding the mechanisms underlying autoantibody development will accelerate therapeutic target identification in autoimmune diseases such as Systemic Lupus Erythematosus (SLE) 1 . Follicular helper T cells (Tfh) have long been implicated in SLE pathogenesis. Yet, a fraction of SLE patients’ autoantibodies are unmutated, supporting that autoreactive B cells also differentiate outside germinal centers (GCs) 2 . Here, we describe a CXCR5 − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
160
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(194 citation statements)
references
References 48 publications
17
160
0
Order By: Relevance
“…By contrast, Caielli et al showed that CXCR3 + Tph cells in SLE patients expressed high IL-10, IFN-γ, and succinate, but no IL-21 or CXCL13, and provided help to B cells in a manner dependent on IL-10 and succinate [61]. The study also showed that the frequency of CXCR3 + Tph cells in the blood was significantly lower in patients with class III and IV nephritis than patients without, and lupus nephritis tissues showed abundant T cells expressing IL-10 adjacent to B cells [61]. Collectively, these observations suggest that Tph cells also contribute to the increase of CD11c + DN B cells in SLE, yet the mechanism might vary among heterogeneous Tph subsets.…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 92%
See 2 more Smart Citations
“…By contrast, Caielli et al showed that CXCR3 + Tph cells in SLE patients expressed high IL-10, IFN-γ, and succinate, but no IL-21 or CXCL13, and provided help to B cells in a manner dependent on IL-10 and succinate [61]. The study also showed that the frequency of CXCR3 + Tph cells in the blood was significantly lower in patients with class III and IV nephritis than patients without, and lupus nephritis tissues showed abundant T cells expressing IL-10 adjacent to B cells [61]. Collectively, these observations suggest that Tph cells also contribute to the increase of CD11c + DN B cells in SLE, yet the mechanism might vary among heterogeneous Tph subsets.…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 92%
“…For example, in inflamed synovial tissues in rheumatoid arthritis, CD4 + T cells that lack CXCR5 but express PD-1 hi and CCR2 (named peripheral helper T cells: Tph) induce memory B cells to differentiate into ASCs in a manner dependent on IL-21 and ICOS [59]. Recent studies showed an increase of CXCR5 − PD-1 hi Tph cells expressing CXCR3 in the blood of active SLE patients [60,61]. Similar to Tph cells in inflamed synovial tissues in rheumatoid arthritis, Lin et al showed that the blood Tph cells in SLE expressed high IL-21 and IFN-γ, and the frequency in the blood correlated with disease activity [60].…”
Section: Cd4 + T-cell Subsets Promoting the Cd11c + Dn B Cell Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of knowledge on the mechanisms underlying MC3T3‐E1 differentiation continues to hinder the progress of MC3T3‐E1‐based therapies for bone regeneration. IL‐10 has profound and indispensable functional effects on infection, inflammation, tissue homeostasis, autoimmunity and cancer . In recent years, the IL‐10 family have been shown to regulate arthritis, suggesting potential effects on osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Succinate is largely used by OXPHOS, which has a reduced activity in the T cells of RA patients and in other autoimmune diseases [74]. A recent study found, in a small subset of CD4 + CXCR3 + CXCR5 -PD-1 hi , T cells in the blood of SLE patients who have increased ROS due to reverse ETC regulated by succinate [75]. A recent study found, in a small subset of CD4 + CXCR3 + CXCR5 -PD-1 hi , T cells in the blood of SLE patients who have increased ROS due to reverse ETC regulated by succinate [75].…”
Section: Oxidative Phosphorylation and Fatty Acid Oxidationmentioning
confidence: 99%